2023
DOI: 10.1186/s12866-023-02860-7
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of β-lactam and fluoroquinolone resistance in various phylotypes of Escherichia coli isolates from urinary tract infections in Jiroft city, Iran

Abstract: Background Urinary tract infection (UTI) is one of the most prevalent infectious diseases with worldwide health threatening. Antimicrobial resistant strains of Escherichia coli (E. coli) are a common cause of UTI which were identified as a treatment challenge. This study aimed to assay the prevalence of common β-lactam resistance genes including blaTEM, blaSHV, blaCTX-M and blaCMY and phenotypic resistance to commonly used β-lactam and fluoroquinolone antibiotics in UTIs. These factors were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…In the present study, the majority of the tested isolates belonged to the phylogenetic group B2 (37%), and group D (25%). In agreement with our results, various studies observed that phylogroup B2 predominated in UPEC, followed by group D [ 8 , 101 103 ]. In contrast, some studies found that phylogroup D is the most prevalent one [ 104 , 105 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the majority of the tested isolates belonged to the phylogenetic group B2 (37%), and group D (25%). In agreement with our results, various studies observed that phylogroup B2 predominated in UPEC, followed by group D [ 8 , 101 103 ]. In contrast, some studies found that phylogroup D is the most prevalent one [ 104 , 105 ].…”
Section: Discussionsupporting
confidence: 93%